2021
DOI: 10.1002/acn3.51461
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in Parkinson‘s disease patients with subjective cognitive complaint

Abstract: Objective Little is known about the disease progression of Parkinson's disease patients with subjective cognitive complaint (PD‐SCC). This longitudinal cohort study aims to compare the progression of clinical features and quality of life (QoL) in PD patients with normal cognition (NC), SCC, and mild cognitive impairment (MCI). Methods A total of 383 PD patients were enrolled, including 189 PD‐NC patients, 59 PD‐SCC patients, and 135 PD‐MCI patients, with 1–7 years of follow‐up. Linear mixed models were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 42 publications
(104 reference statements)
1
31
1
Order By: Relevance
“…The prevalence of SCD was 28.1% in our de novo PD cohort, which is slightly higher than previous findings 11–13 . This may be due to heterogeneity in assessing PD‐SCD questions.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The prevalence of SCD was 28.1% in our de novo PD cohort, which is slightly higher than previous findings 11–13 . This may be due to heterogeneity in assessing PD‐SCD questions.…”
Section: Discussioncontrasting
confidence: 78%
“…Given that most previous studies allow for concurrent objective impairment, 8–10 the prevalence and affective correlates of SCD remain unclear. To date, only a few studies have estimated the prevalence of PD‐SCD, with results ranging from 15.4% to 27.2% 11–13 . Furthermore, although several studies have reported that PD‐SCD is associated with severe anxiety/depression symptoms, 8,13–15 this relationship is debated due to inconsistent reports 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…10 Cognitive impairment in PD also affects multiple cognitive domains, [29][30][31] and the term "cognitive" is recommended to indicate subjective impairment. In the selected studies of this review, the term "SCCs" was the most frequently used (10 studies), [32][33][34][35][36][37][38][39][40][41] and "subjective memory complaints (SMCs)" [42][43][44][45][46] and "SCD" 37,47-50 were both used in five studies each. Mills et al 37 used both "SCCs" and "SCD. "…”
Section: Terminologies For Subjective Cognitive Complaintsmentioning
confidence: 99%
“…32,36,39,41 Among them, four studies assessed SCCs using part of a large scale: the Nonmotor Symptoms Questionnaire 52 Item 12 43 and the MDS-Unified PD Rating Scale (UP-DRS) 53 question 1.1. 32,36,41 Two studies used questions on patients' performance in five 47 or seven 45 cognitive domains. Ten studies assessed SCCs using questionnaires administered to patients: Non-Motor Symptoms Scale for Parkinson's Disease 54 domain 5 (two studies), 33,34 Memory Complaints Questionnaire 55 (one study), 42 Neurobehavioral Inventory (NBI) 56 (two studies), 32,35 Quality of Life in Neurological Disorders 57 -Cognition: General Concerns and Cognition: Executive Function (one study), 37 Forgetfulness Assessment Inventory 58 (one study), 46 Subjective Cognitive Decline Questionnaire (one study), 50 Cognitive Complaint Interview 59 (one study), 38 and Parkinson's Disease Cog-nitive Functional Rating Scale 60 (one study).…”
Section: Assessment Of Subjective Cognitive Complaintsmentioning
confidence: 99%
“…Depressive symptoms may precede CI in de novo PD patients (Jones et al 2019 ), and there is a relationship between early depression with motor worsening and cognitive decline (Fernandez et al 2009 ; Ng et al 2015 ). That, however, can also be a precursor of depressive symptoms in PD (Han et al 2021 ; Petkus et al 2019 ; Schroeders et al 2022 ). CI and depressive symptoms are associated with increase in the severity of PD, and depressive symptoms are associated with an increase in CI (Sinaeefar et al 2021 ).…”
Section: Pd-depression and Other Symptomsmentioning
confidence: 99%